Global Trends and Research Dynamics of Community-Based Health Literacy - Ahmadi Ahmadi; Mei Lestari Ika Widyyati (Health and Technology Journal (HTechJ), 2026)
Community-based health literacy has emerged as a critical determinant of public health outcomes, particularly amid global health crises and the rapid evolution of the digital information landscape. Despite a growing body of literature, the intellectual structure, thematic evolution, and patterns of scientific collaboration in this field remain insufficiently systematized. This study aims to analyze global trends, themes, collaboration patterns, and scientific impact of community-based health literacy research from 2007 to 2026 using a bibliometric approach. This study employs a bibliometric analysis of 173 articles indexed in the Scopus database from 2007 to 2026. Articles were selected through title and abstract screening based on predefined inclusion criteria. Data analysis was conducted using Microsoft Excel for descriptive statistics, VOSviewer for mapping collaboration networks and keyword co-occurrence, and Biblioshiny for assessing publication trends and citation metrics. The findings reveal a marked acceleration in publication output after 2020, with a peak in 2025. Geographically, research production is highly concentrated in China and the United States, both of which also occupy central positions within global collaboration networks. Thematic analysis indicates a predominance of quantitative, survey-based methodologies, with the COVID-19 pandemic acting as a major driver of research activity. Temporal trends demonstrate a gradual shift from crisis-oriented studies toward digital health communication and information dissemination, although methodological approaches remain relatively unchanged. Community-based health literacy research is undergoing rapid expansion and increasing thematic diversification; however, it remains characterized by geographic concentration and limited methodological innovation. Future research should prioritize more inclusive international collaboration and the development of longitudinal and interventional study designs to enhance conceptual maturity and global applicability in this field.